Synthesis of zinc selenide/graphene oxide composite via direct and indirect hydrothermal method - Lee, Han Kee; Liew, Josephine Ying Chyi; Zainal Abidin Talib; Mohammad Shuhazlly Mamat; Lim, Janet Hong Ngee; Fakhrurrazi Ashari; Leong, Yong Jian; Chang, Fu Dee; Burhanuddin Yeop Majlis (Penerbit Universiti Kebangsaan Malaysia, 2016)
Zinc selenide/graphene oxide (ZnSe/GO) composite is synthesized using hydrothermal method. Two different methods such as direct and indirect route have been investigated to form the ZnSe/GO composite. In this research, the graphene oxide used was in sheet and liquid form. The synthesized composite was then characterized using X-ray diffraction (XRD) for phase identification, field emission scanning electron microscopy (FESEM) for morphology analysis and ultraviolet-visible spectroscopy (UV-Vis) for optical properties. ZnSe/GO composite showed absorption peak ranging from 460 to 480 nm with the optical band gap obtained through Tauc equation. The optical band gap of the ZnSe/GO composite has been tuned down to a smaller value as compared to the bulk ZnSe compound. The optical band gap has been reduced to around 2.53 eV when liquid graphene oxide was used while around 2.23 to 2.32 eV when graphene oxide sheet was used. The purity of ZnSe/GO composite synthesis via indirect hydrothermal method is higher than those synthesized via direct hydrothermal method. The type of graphene oxide will affect the morphology of the composite where the ZnSe compound was either wrapped by tiny thorn-like substance or graphene oxide layer.